A Frommian perspective on the socio-psychological structure of post-fascism in liberal democracies. Issue 2 (3rd May 2020) - Sakurai, Takamichi
ABSTRACT: My research explores Erich Fromm's social theories of narcissism, alienation and authoritarianism for the purpose of linking those theories together, thereby analysing current populist phenomena as an extension of a fascist development in terms of Enzo Traverso's conception of post-fascism. In my view, Fromm's critical social theory of narcissism, which pertains to his two other theories, has great potential to unravel current political issues in liberal democracies that are generally tackled in terms of populism. Through a demonstration of the theoretical scope of Fromm's social theory, which sheds light on pathological social and political phenomena in historical continuity, I argue that the primary tasks of Critical Theory in Frommian terms are to divulge the sources of fascist orientations in seemingly democratic practice and to offer appropriate remedies for these difficulties. In this light, I conclude that in terms of a Frommian social theory of narcissism, fascist types of politics thrive even in advanced liberal-democratic countries, taking the form of authoritarian populism, particularly where society rests on a narcissistic character structure intertwined with an authoritarian orientation.